2020
DOI: 10.20944/preprints202003.0385.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric Transport, a Major Pathway of Microplastics to Remote Regions

Abstract: In recent years, marine, freshwater and terrestrial pollution with microplastics has been discussed extensively, whereas atmospheric microplastic transport has been largely overlooked. Here, we present the first global simulation of atmospheric transport of microplastic particles produced by road traffic (TWPs – tire wear particles and BWPs – brake wear particles), a major source that can be quantified relatively well. We find a high transport efficiency of these particles to remote regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The great part of microplastic contamination responds to the atmospheric contribution in the productive processes [24,42,45]. Air currents transport large amounts of microparticles from the places of high contamination that end up in food, even more so when atmospheric contamination is not a controlling factor in industrial production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The great part of microplastic contamination responds to the atmospheric contribution in the productive processes [24,42,45]. Air currents transport large amounts of microparticles from the places of high contamination that end up in food, even more so when atmospheric contamination is not a controlling factor in industrial production.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the incidence of microplastics, different researchers studied honey, beer and table salt in Europe and China. Bottled and tap water was assessed on all continents by an American research group, who demonstrated that the presence of plastic can begin to compete with greenhouse gases in terms of ubiquity and impact on environmental deterioration [24].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, abundant MPs have been detected from the supraglacial debris of the Forni Glacier (Italian Alps) (Ambrosini et al, 2019), European and Arctic snow (Bergmann et al, 2019), and precipitation in the protected areas of the United States (Brahney et al, 2020). These results suggest that atmospheric long-range transport (or airborne pathways) and deposition can be a significant and nonnegligible pathway for MPs in the environment (Evangeliou et al, 2020;Hale et al, 2020;Wright et al, 2020).…”
Section: Main Textmentioning
confidence: 99%
“…It is surrounded by regions dominated by the production of plastics (China and other Asian countries) and the dismantling of commercial ships (South Asia, India, Bangladesh, and Pakistan) (PlasticEurope, 2019). The recognition of MP pollution in the remote area of the TP might be an important scientific issue and a relevant topic in addressing the global plastic cycle (Allen et al, 2019;Evangeliou et al, 2020;Bank and Hansson, 2019). However, studies on MPs in high-altitude glaciers of this remote area have not been reported yet.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation